Investigating the Current Usage and Challenges in Adopting Radio Frequency Identification (RFID) Technology in University Libraries of Pakistan - Muhammad Nadeem Akhtar; Ghulam Farooque Channar; Dr. Muhammad Naushad Sabzwari; Sidra Batool; Ferhana Saeed Hashmi; Muhammad Waqar Aslam; Khurram Shahzad, (Dialogue Social Science Review (DSSR), 2025)
This study investigates the current usage and challenges in adopting Radio Frequency Identification (RFID) technology in university libraries across Pakistan. The research focused on library professionals from 41 university libraries, with data analyzed using descriptive and inferential statistics through SPSS. The findings revealed a positive attitude among library professionals towards RFID implementation, recognizing its potential to enhance library services in terms of quality and efficiency. However, several barriers were identified, including high costs of RFID components, lack of funding, inadequate training facilities, and technological infrastructure challenges. Despite these obstacles, library professionals strongly believe in RFID's benefits, particularly in improving material tracking, safeguarding, and overall service delivery. The study also highlighted concerns regarding data security, privacy, and staff attitudes, which complicate the technology's adoption. The results suggest that addressing funding shortages, improving training opportunities, and enhancing technological infrastructure are crucial for successful RFID adoption. The study's implications emphasize the need for better training, funding, and technical expertise to fully harness RFID's potential, offering valuable insights for library professionals, policymakers, and researchers in the field of library science. This research contributes to the growing body of literature on RFID in library settings and provides a foundation for future studies and practical applications in Pakistani university libraries.